Pengaruh Pelatihan, Kemampuan Kerja dan Komitmen Organisasi Terhadap Kinerja Pegawai SNVT PJSA WS. IAKR Prov. Sumbar - Martha Siska; Yulihasri Yulihasri; Zuripal Zuripal (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
This research is based on the not yet optimal performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra marked by the target and the realization of the performance is not appropriate. Based on indicators of 7 targets of employee performance with targets from agency programs of 100 on average only 84% realized. Based on this, there are three factors suspected of causing this, including training, work ability and organizational commitment. This study aims to see the effect of (1) Training on the performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra (2) Work ability on the performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra (3) Organizational commitment to the performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra 4) Training, work ability and organizational commitment have a joint effect on the performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra. The population in this study were all employees of SNVT PJSA WS. IAKR Prov. West Sumatra as many as 38 people. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity. The results of this study indicate that (1) Training has a significant positive effect on the performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra (2) Work Ability has a positive influence on the Performance of SNVT PJSA WS Employees. IAKR Prov. West Sumatra (3) Organizational commitment has a positive effect on the performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra (4) Training, work ability and organizational commitment together have a positive effect on the performance of SNVT PJSA WS employees. IAKR Prov. West Sumatra.